CVD and diamond tips: can then influence the bond strength of a total-etch adhesive to dentin? - Schirlei de Carvalho Rocha; Daphne Camara Barcellos; César Rogério Pucci; Clovis Pagani; Dimas Renó de Lima (Brazilian Dental Science)
Data (MPa) were analyzed by two-way ANOVA (Surface treatment X Etching time) and Tukey's test (5%). Results and conclusions: Surface treatment with CVD tips (27.70 ± 4.04a) produced significantly higher bond strength values compared to diamond tips (23.96 ± 5.83b), and 5 second etching time on dentin produced similar bond strength values when compared to 10 and 15 second etching times. Objectives: Evaluate the microtensile bond strength of a total-etch adhesive to dentin, using a CVD tip and a diamond tip to use in dentin preparation and varying the etching time. Material and method: The dentin from the buccal face of sixty bovine teeth was exposed and prepared using two different methods (n=30): Group 1 (DT) – a diamond tip on a high-speed handpiece; and Group 2 (CVD) – a CVD tip on an ultrasonic handpiece. Each group used 37% phosphoric acid and was divided into three subgroups, according to the etching time (n=10): Subgroup 5 - 5 seconds; Subgroup 10 - 10 seconds; and Subgroup 15 - 15 seconds. The teeth were restored with Single Bond adhesive and the composite resin Herculite Classic. The specimens were subjected to thermomechanical wear (mechanical cycling/100.000 cycles, thermal cycling/1.000 cycles). Stick-like specimens were obtained and submitted to a microtensile test in a universal testing machine.